Differential association of cortisol with visual memory/learning and executive function in Bipolar Disorder. (January 2022) - Tournikioti, Kalliopi; Alevizaki, Maria; Michopoulos, Ioannis; Mantzou, Aimilia; Soldatos, Constantin R.; Douzenis, Athanasios; Dikeos, Dimitris; Ferentinos, Panagiotis
Highlights: Glucocorticoid receptor density is higher in hippocampus than in prefrontal cortex. Visual memory and planning depend on hippocampus and prefrontal cortex, respectively. Basal cortisol may be differentially associated with visual memory and planning. We used CANTAB tasks for visual memory (PAL) and planning (SOC) in bipolar patients. Higher basal cortisol was associated with worse performance in PAL but not in SOC. Abstract: The association of cortisol with cognition has been understudied in Bipolar Disorder (BD); available evidence is inconsistent while it is unknown whether cortisol's effects vary across neurocognitive domains implicating different brain structures. This study aimed to examine the association of cortisol with two cognitive tasks targeting visual memory and executive function (planning) in BD, related to the hippocampus and prefrontal lobe, respectively. Cambridge Neuropsychological Test Automated Battery (CANTAB) tasks targeting paired associative learning (PAL) and planning (Stockings of Cambridge; SOC) were administered to 60 BD type I patients. Basal serum cortisol was also measured. Higher cortisol was associated with worse performance in PAL, but not SOC, after controlling for gender, education, illness duration and treatment with mood stabilizers. This is the first study to examine the association of cortisol with neurocognitive function in BD while controlling for clinicodemographic and treatment-related factors. We found a significant association of cortisol with hippocampal-related visual memory/learning but not with prefrontal lobe-related executive function, suggesting domain-specific underlying mechanisms of cognitive dysfunction in BD. Future studies should further explore cortisol's brain structure-specific effects on cognitive functioning in BD.